RETRACTED: Enhancing Concrete Strength with Polymer-Based Additives in the Cement Matrix: A Comprehensive Review (Journal of Civil Engineering Researchers, 2025)
The modern types of concrete consist of a mixture of aggregates, cement, water, and optional additives and admixtures. Polymer additives, such as superplasticizers, latexes, redispersible powders, polymer fibers, and recycled polymers, have shown promise in significantly altering the properties of concrete and mortar. These polymeric materials are widely used in the construction industry to enhance resistance to cracking and improve overall performance. This paper provides an overview of popular polymeric additives and their impact on concrete properties, as well as the relationship between the chemical structure of additives and the behavior of the resulting concrete.
Keywords: Cement; additives; Superplasticizers; Polymer; Concrete additives; Redispersible powders